2017
DOI: 10.1051/sicotj/2017006
|View full text |Cite
|
Sign up to set email alerts
|

Kerboull-type plate in a direct anterior approach for severe bone defects at primary total hip arthroplasty: technical note

Abstract: Introduction: For cases with extensive acetabular bone defects, we perform surgery combining the Kerboull-type (KT) plate and bone graft through direct anterior approach (DAA) in primary total hip arthroplasty (THA) requiring acetabular reconstruction as minimally invasive surgery. This paper provides the details of the surgical procedure. Methods: The basic structure of the Kerboull-type plate is a cruciform plate. Since the hook of the Kerboull-type plate has to be applied to the tear drop, a space for it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Therefore, Wegrzyn et al advocated reconstructing the acetabulum with the use of a Kerboull cross-plate, which does not rely on bone ingrowth for stability and reduces the mechanical forces applied to the periacetabular bone with fixation over a large surface area of intact pelvic bone, increasing the elasticity of the reconstruction [ 2 ]. Matsumoto et al reported the details of surgical acetabular reconstruction using a KT plate through the DAA for patients with an extensive acetabular bone defect [ 3 ]. No serious complications, such as dislocation, infection, or periprosthetic femoral fracture, occurred in any patient after surgery [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, Wegrzyn et al advocated reconstructing the acetabulum with the use of a Kerboull cross-plate, which does not rely on bone ingrowth for stability and reduces the mechanical forces applied to the periacetabular bone with fixation over a large surface area of intact pelvic bone, increasing the elasticity of the reconstruction [ 2 ]. Matsumoto et al reported the details of surgical acetabular reconstruction using a KT plate through the DAA for patients with an extensive acetabular bone defect [ 3 ]. No serious complications, such as dislocation, infection, or periprosthetic femoral fracture, occurred in any patient after surgery [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Matsumoto et al reported the details of surgical acetabular reconstruction using a KT plate through the DAA for patients with an extensive acetabular bone defect [ 3 ]. No serious complications, such as dislocation, infection, or periprosthetic femoral fracture, occurred in any patient after surgery [ 3 ]. Furthermore, in this case, antibiotic-laden bone cement was used at the time of definitive component implantation to prevent prosthetic joint infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of fluoroscopy for accurate implant placement has been demonstrated, and we always use it when DAA is employed [22]. We previously reported the detailed surgical procedure of acetabular reconstruction with the Kerboull-type plate through DAA [23]. No serious complications, such as dislocation, infection, or periprosthetic femoral fracture, occurred in any patient after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For THA, a dual mobility cup was used for the acetabular component: the MDM (Stryker Orthopaedics, Mahwah, New Jersey, USA) in 4 patients and the G7 (Zimmer Biomet, Warsaw, Indiana, USA) in 14 patients. Surgery was performed through DAA in the supine position using a traction table and intraoperative uoroscopy [13] (Fig. 2).…”
Section: Operative Procedures and Implant Informationmentioning
confidence: 99%